STRATEGY FOR DEVELOPING THE DATO BEACH TOURIST ATTRACTION IN INCREASING LOCAL REVENUE IN MAJENE REGENCY WEST SULAWESI - Afdaliyah, Nur; Rukmana, Novayanti Sopia; Nur, Andi Cudai (Universitas Negeri Makassar, 2025)
This writing aims to find out the strategy for developing the Dato beach tourist attraction in increasing PAD. The type of research used is descri ptive qualitative, while the data sources used in this research are primary data sources and secondary data sources with a total of nine informants. Data collection techniques use observation, interviews and documentation methods. The data analysis techniques used in this research are data reduction, data presentation, and drawing conclusions. Validation of the data used is source triangulation. Based on the results of the research that has been carried out, it shows that there are several strategies for developing the Dato beach tourist attraction, for example strategies for carrying out promotions on various social media, where this strategy is quite good for the development of the Dato beach tourist attraction, seen from the increase in tourist visits. The Majene Regency tourism awareness group (Pokdarwis) also has several strategies for developing Dato beach tourist attractions, for example making tracking or bridges over the water, making viewing towers, and also adding several facilities, for example lodging for tourists who want to enjoy Dato beach for longer. Food stalls are also available so you don't need to worry about food because the food stalls here provide a variety of foods. Based on the results of this research, it is recommended that the government pay more attention to the development of tourist attractions in Majene district, including Dato beach, because this beach has quite good potential for development, this could be in the form of updating facilities such as adding sales of typical Mandar souvenirs which can be used as souvenirs for visitors. those from outside the area. Apart from that, human resource training still needs to be improved because community participation and public awareness in maintaining tourist attractions is still lacking